Let the other end point be (x,y)
THe two endpoints are in a straight line where the Center would be the MIDPOINT of them.
Thus, we can say
(2, 5) ----------- (5,1) ----------- (x,y)
We can use midpoint formula here, which is:
Midpint Formula:
![((x_1+x_2)/(2)),((y_1+y_2)/(2))](https://img.qammunity.org/2023/formulas/mathematics/high-school/szyd6f2govurdmvvovm4mlbeapsc1c2sw4.png)
So,
![\begin{gathered} (2+x)/(2)=5 \\ 2+x=10 \\ x=10-2 \\ x=8 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/euvuyd5b2mg0ytbkv9b72ogea9kvrc0fi8.png)
and
![\begin{gathered} (5+y)/(2)=1 \\ 5+y=2 \\ y=2-5 \\ y=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/zouiotwbv08dozagrbf0cfqyuw7tahhvf4.png)
Hence the midpoint is (8, -3)